2008
DOI: 10.1177/1538574407306797
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Selective Surveillance Colonoscopy in the Early Diagnosis of Colonic Ischemia After Successful Ruptured Abdominal Aortic Aneurysm Repair

Abstract: Our study showed that CI is a frequent complication after successful rAAA repair and could reliably be early diagnosed if surveillance colonoscopy was offered selectively in patients with more than three PRFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
18
1
Order By: Relevance
“…Dadian et al identified intra-operative hypotension of <70mmHg as associated with IC [19] . Three studies identified that massive transfusion was associated with increased rates of IC [19,20,15] . All of these were retrospective singlecentre observational studies.…”
Section: Pre-operative Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dadian et al identified intra-operative hypotension of <70mmHg as associated with IC [19] . Three studies identified that massive transfusion was associated with increased rates of IC [19,20,15] . All of these were retrospective singlecentre observational studies.…”
Section: Pre-operative Factorsmentioning
confidence: 99%
“…The odds ratio of developing IC if hypotension lasted for 30 minutes or more ranged from 1.26-30 [16,18,15] . Dadian et al identified intra-operative hypotension of <70mmHg as associated with IC [19] .…”
Section: Pre-operative Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Therefore, other authors have recommended sigmoidoscopy in patients with specific risk factors. 7,12 It remains unclear whether sigmoidoscopy has actually improved, or possibly worsened the clinical outcome of patients in the present study. Performing sigmoidoscopy carries the risk of delaying the time to bowel resection, and possible worsening of CI.…”
Section: Discussionmentioning
confidence: 72%
“…Some endovascular series have shown higher rates [110] due to an inability to evacuate retroperitoneal haematoma. Risk factors include hypotension, hypothermia, acidosis, aggressive fluid ⁄ blood product resuscitation, anaemia [1,111,112] and the need for an aortic occlusion balloon [110]. Some authors recommend postoperative monitoring of intra-abdominal pressure via bladder pressure [1,113,114] or even surveillance colonoscopy in patients at increased risk [111,115].…”
Section: Postoperative Managementmentioning
confidence: 99%